The sustainable development goals and nursing - Hamdia Mirkhan Ahmed (Hawler Medical University, 2018)
The Sustainable Development Goals (SDGs) were adopted by the United Na-tions in 2015 to replace the Millennium Development Goals (MDGs). They contain 17 goals covering a broad range of sustain-able development issues for the world, such as ending poverty, hunger, improving health and education, combating climate change, etc. The 191 UN Member States have agreed to achieve these new goals by 2030. Health has a central place in SDG 3: Ensure healthy lives and promote wellbe-ing for all ages, and clearly nursing has a major role to play in relation to SDG 3. But the work of nurses also has a major impact on the delivery of other SDGs such as edu-cation and poverty - these are often re-ferred to as the social determinants of health (SDH). The SDH are the conditions in which people are born, grow, work, live and impact on the conditions of health and daily lives. While nurses seek to help peo-ple achieve their optimal health, our work frequently includes addressing the SDH and nurses understand the links between wider conditions and individual and population health.